Art in Japan Today 1985-1995. - Yaguchi, Kunio; Shioda, Junichi; Kumagai, Isako (Tokyo : Museum of Contemporary Art, 1995)
Araki, Nobuyoshi ; Cai, Guo Qiang ; Endo, Toshikatsu ; Fukuda, Miran ; Funakoshi, Katsura ; Kasahara, Emiko ; Kawamata, Tadashi ; Matsui, Chie ; Miyajima, Tatsuo ; Morimura, Yasumasa ; Nagasawa, Hidetoshi ; Nakamura Kazumi ; Sugimoto, Hiroshi ; Tatsuno, Toeko ; Tsuchiya, Kimio ; Toya, Shigeo ; Yanagi, Yukinori ; Yoshizawa, Mika
Inaugural Exhibition Art in Japan Today 1985-1995, Museum of Contemporary Art, Tokyo, 19 March - 21 May 1995
English-Japanese
kunstcatalogus
Keywords: Japan